Infant feeding practices in an urban tertiary care hospital: A descriptive longitudinal study - Hegde, Jayashree; Manjula, L; Venkatesha, K R (Indian Journal of Child Health, 2017)
Background: Infant and young child feeding are the corner stone for child development. More than a third of the world’s undernourished children reside in India. Inadequate infant and young child feeding practices with inadequate care and management of common illnesses contributes to malnutrition. Objective: To study the prevailing infant feeding practices and determine influence of factors on infant feeding in a tertiary care hospital. Materials and Methods: A descriptive longitudinal follow-up study was conducted in a tertiary care hospital between November 2010 and April 2012. Maternal and baby’s profiles were obtained using oral questionnaire after birth by personal one-to-one interview. These cases were followed up for their infant feeding practices till 1 year of age in outpatient department and also by telephonic conversation. Continous variables were analysed by mean and SD. For categorical variable frequency and percentage were determined. Results: 61.25% mothers had initiated breastfeeding within 1 h. Prelacteal feed was given to 28.6% babies. 61.5% had initiated complementary feed at 6 months. Bottle feeding was preferred mode of feeding. There was a statistically significant association between initiation of breastfeeding and parity (p=0.022) and type of delivery (p<0.0001), religion and complementary feeding introduction (p<0.001), religion and duration of exclusive breastfeeding (EBF) (p=0.003), occupation and EBF duration (p=0.005), education (p=0.015), and religion (p=0.001) were associated with prelacteal feeds. Conclusions: Infant feeding practices observed from the study include early initiation of breastfeeding, appropriate duration of EBF, and timely introduction of complementary feed. Practice of prelacteal and bottle feeding was seen. Infant feeding practices are found to be influenced by several socio-demographic factors.